Penerapan Kurs Tetap dan Kurs Bebas Dalam Menentukan Keseimbangan Nilai Tukar Mata Uang - Edalmen (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 1999)
In general trade between nations can occur only if it is possible to exchange the currency of one nation for that of the other. The exchange of one currency to another one is called a foreign exchange transaction. The exchange rate is determined by the equality between supply and demand for currency which is called the Flexible Exchange Rate. The exchange rate used to maintain the exchange rate at a particular value is said the Fixed Exchange Rate.